Evaluating the effectiveness of a traumatic brain injury awareness campaign among university students - Jaffer, Usman; Nordin, ‘Athira Najwa; Zulfikar, Haziqah Husna; Mohamad Faisal, Muaz Faisal; Mohd Yunus, Nurul Nadzeera; Usman, Nur Suryati; Ahmad Rafiee, Siti Aisyah Aqilah; Che Mohd Nassir, Che Mohd Nasril; Ahmed, Mohamed Ayaaz; Ahmad H.Osman, Rahmah (Global Academic Excellence, 2024)
Traumatic Brain Injury (TBI) remains a significant public health challenge globally, often leading to profound physical, cognitive, and psychosocial impacts. This study examined the effectiveness of a brief TBI awareness campaign within a university setting. A total of 37 participants, including students, high-risk occupation workers, caregivers, and members of the general public, took part in both online and in-person sessions. A mixed-methods approach was employed, integrating semi-structured interviews, a pre-test/post-test questionnaire based on Linden and Crothers’ (2006) instrument, and thematic analysis of participants’ qualitative feedback. Quantitative findings indicated no statistically significant difference in perceptions of TBI survivors before and after the campaign, potentially attributable to a short intervention duration and a modest sample size. However, qualitative data revealed that many participants perceived the campaign content to be engaging, expressed increased empathy towards TBI survivors, and reported intentions to adopt risk-reducing behaviours or advocate for TBI awareness. These results underscore the promise of targeted educational initiatives but also highlight the need for longer and more diverse campaigns to facilitate more robust knowledge retention and behaviour change. Future research should extend the campaign’s duration, explore different modes of engagement (e.g., video testimonies, interactive technologies), and involve broader, more representative populations to yield more generalisable and enduring outcomes.